The Effect of Finger Mathematics and Audiovisual Materials on the Understanding of Multiplication Concepts Among Students with Mild Dyscalculia in Elementary School - Martin Restuningsih; Eges Triwahyuni; Eric Dwi Putra (Jurnal Penelitian Pendidikan IPA, 2026)
Mathematics is a crucial intellectual tool in daily life and serves as the foundation for various academic disciplines. This issue is also faced by students at SDN Patemon 01 Jember, including those with mild dyscalculia. Based on the author’s observations, data revealed that 10% of students experience difficulties with numerical learning. The objective of this study is to examine the influence of Jarimatika and audiovisual media on the concept of multiplication among students with mild dyscalculia. This study was designed as an experimental study aimed at tracing the impact of applying the Jarimatika method and using audiovisual media on students’ cognitive abilities. Based on the results of data analysis and discussion in this study, it can be concluded that the application of the Jarimatika method (X1) and audiovisual media (X2) has a positive and significant effect, both partially and simultaneously, on students’ understanding of the concept of multiplication (Y). The synergy of this integrative approach has proven effective as an instructional remediation strategy, contributing 61.2% of the total effect (R² = 0.612), while the remainder is influenced by factors outside the research model. This combination involves sensory coordination through tactile-kinesthetic finger movement activities and visual-auditory stimulation from digital displays.